Pengembangan Modul Pembelajaran Geometri berbasis Etnomatematika di kelas V - Mario Florentino; Agung Lukito; Neni mariana (LP. Ma'arif Janggan Magetan, 2022)
This research is motivated by the low interest in learning of fifth grade students in mathematics, limited teaching materials that facilitate students in constructing their knowledge, especially teaching materials based on ethnomathematics, and students are still difficulties in solving mathematical problems related to geometry. The purpose of this study was to produce an ethnomathematics-based geometry learning module in class V and describe its quality in terms of validity, practicality, and effectiveness. The module specifications developed are, (1) An ethnomathematics-based geometry learning module which contains geometry material for grade V Elementary School students which consists of 3 learning activities, namely recognizing flat shapes, identifying shapes and elements of flat shapes, and identifying relationship between flat shapes, (2) The developed learning module contains woven fabric motifs in Sikka village which are integrated into geometry material in class V so that it can make it easier for students to understand the contents of the module. The research procedure adapts the ADDIE development model, namely the development model which consists of five stages which include analysis (analyze), design(development), implementation (implementation), and evaluation (evaluation). In terms of validity, based on the validation results of media experts and material experts, at least they get a good score so that they are included in the valid category. From a practical standpoint, based on the practicality assessment sheet by the teacher as a minimum user, he gets a good score. Based on the student response questionnaire 96% chose to strongly agree and 4% chose to agree so that the learning module was declared practical. In terms of effectiveness, after going through the implementation phase, a pre-test score of 49.37 and a post-test score of 79.06 were obtained with a presentation of 100% student learning completeness. Then the test results using the N-gain obtained a value of 0.83 which is based on the N-gain including high and very effective. Based on the results of this study, it can be concluded that the ethnomathematics-based geometry learning module in class V using the ADDIE development model meets valid, practical, and effective criteria so it is feasible to use.